Crucible - James Rollins (William Morrow / Harper Collins Publishers, 2019)
Arriving home on Christmas Eve, Commander Gray Pierce discovers his house ransacked, his pregnant lover missing, and his best friends wife, Kat, unconscious on the kitchen floor. With no shred of evidence to follow, his one hope to find the woman he loves and his unborn child is Kat, the only witness to what happened. But the injured woman is in a semi-comatose state and cannot speak-until a brilliant neurologist offers a radical approach to "unlock" her mind long enough to ask a few questions. What Pierce learns from Kat sets Sigma Force on a frantic quest for answers that are connected to mysteries reaching back to the Spanish Inquisition and to one of the most reviled and blood-soaked books in human history-a Medieval text known as the Malleus Maleficarum, the Hammer of Witches. What they uncover hidden deep in the past will reveal a frightening truth in the present and a future on the brink of annihilation, and force them to confront the ultimate question: What does it mean to have a soul?....